Highly luminescent polyethylene glycol-passivated graphene quantum dots for light emitting diodes. Issue 46 (22nd July 2020) - Kim, Hyun Jun; Lee, Chung Kyeong; Seo, Jin Gwan; Hong, Soon Jik; Song, Gian; Lee, Junghoon; Ahn, Changui; Lee, Dong Ju; Song, Sung Ho
Abstract : We prepared blue-photoluminescent polyethylene glycol GQDs (PEG-GQDs) through PEG surface passivation. The PL intensity was stronger than that of pristine GQDs. These were then used as LED emitters and the fluorescence mechanism was investigated. Abstract : The emergence of fluorescent graphene quantum dots (GQDs) is expected to enhance the usefulness of quantum dots (QDs), in terms of their unique luminescence, photostability, low toxicity, chemical resistance, and electron transport properties. Here we prepared blue-photoluminescent polyethylene glycol GQDs (PEG-GQDs) through PEG surface passivation. The photoluminescence (PL) quantum yield (QY) of PEG-GQDs with 320 nm excitation was about 4.9%, which was higher than that of pure GQDs. The as-fabricated PEG-GQDs with high QY were then used as light-emitting diode (PGQD-LED) emitters, in which the GQDs were incorporated into polymeric host layers in a multilayer electroluminescent device; blue emission with a luminance exceeding 800 cd m −2 was achieved, thus demonstrating the potential of PEG-GQDs as emitters in electroluminescence applications. Furthermore, the fluorescence mechanism of PEG-GQDs was investigated and proved that the origin of strong fluorescence of PEG-GQDs is associated with the luminescence from intrinsic states. The highly fluorescent PEG-GQDs will allow new devices, such as multicolor LEDs, to be developed with extraordinary properties, by tailoring the intrinsic and extrinsic states.